2018
DOI: 10.1186/s12955-018-0840-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the child’s perceived general health on the primary caregiver’s health status

Abstract: BackgroundIn estimating the impact of an intervention, ignoring the effect of improving the health of one member of the caregiver/child dyad on the Health Related Quality of Life (HRQoL) of the other member may lead to an underestimation of the utility gained. This may be particularly true for infants/young children and their caregivers. The aim of this study was to quantify the interaction between the child’s perceived general health as assessed by the newly developed Toddler and Infant Questionnaire (TANDI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Further research into how these non-observable elements could best be captured by proxy reports may be valuable, but the research would need to involve decision-makers to consider whether the broader information on quality of life was sufficiently valid and reliable. Another challenge is that it is not possible to fully separate the influence of the carer-child dyad upon each other [ 28 , 29 , 30 , 31 ]. A seriously unwell child is likely to negatively affect the parent’s health-related quality of life, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Further research into how these non-observable elements could best be captured by proxy reports may be valuable, but the research would need to involve decision-makers to consider whether the broader information on quality of life was sufficiently valid and reliable. Another challenge is that it is not possible to fully separate the influence of the carer-child dyad upon each other [ 28 , 29 , 30 , 31 ]. A seriously unwell child is likely to negatively affect the parent’s health-related quality of life, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the child's health was found to be greater than the caregiver's self-reported problems with their own pain and discomfort or mobility. Furthermore, the results showed that the general health scores of children who were acutely ill were strongly associated with the caregiver's general health score and preference-based scores (Verstraete, Jelsma & Ramma 2018a). This result was surprising as most of the literature focusses on the effects of caring for a chronically ill child and not acutely ill children.…”
Section: Introductionmentioning
confidence: 92%
“…The influence of the acutely ill child's health on the caregiver's health has not been widely researched, and as the study by Verstraete et al (2018a) was cross-sectional, there was no evidence that improving the health of the child would in fact improve the health of the caregiver relating to an increase in the societal QALY gained. The methodology of our study collected longitudinal data to explore this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The Eurobarometer (2012) survey revealed that health leads the list of values associated with happiness in all European member states assessed except Denmark, where respondents first mention love. Several studies relate SGH with the human values of Stimulation (e.g., Sagiv and Schwartz 2000), Hedonism (e.g., Pino-Domínguez et al 2016), Achievement (e.g., Minkkinen et al 2017), Power (e.g., Verstraete et al 2018), Security (e.g., Norlander et al 2015), Conformity (e.g., del Pilar Sánchez-López et al 2014), Tradition (e.g., Baiocchi-Wagner andOlson 2016), Benevolence (e.g., Bevan and Sparks 2014), and Universalism (e.g., Hughes 2017).…”
Section: Human Values and Subjective General Health (Sgh)mentioning
confidence: 99%
“…One's values depend on where a person was during the value formation age (0-20 years) and what that person experienced during that time (Gibson et al 2009). Values first vary between individuals, second between nations, and third between regions within nations (Vignoles et al 2018).…”
Section: Introductionmentioning
confidence: 99%